Prevalence and associations of classic psychedelic-related seizures in a population-based sample. (1st October 2022) - Simonsson, Otto; Goldberg, Simon B.; Chambers, Richard; Osika, Walter; Long, Dustin M.; Hendricks, Peter S.
Abstract: Objectives: Previous studies have reported links between classic psychedelic use and seizures, but little remains known about prevalence and potential risk factors of classic psychedelic-related seizures. Methods: Using a sample representative of the US adult population with regard to sex, age, and ethnicity ( N  = 2822), this study examined the prevalence and potential risk factors of classic psychedelic-related seizures, in a subsample of respondents who reported lifetime classic psychedelic use ( n  = 613). Results: Among those who reported lifetime classic psychedelic use, 1.5 % reported classic psychedelic-related seizures, a statistic that comports with the prevalence of epilepsy in the US population. Among those who reported seizures while using a classic psychedelic, almost half reported co-use of antidepressants, mood stabilizers, or opioid replacement therapies at the time of the seizures. Notably, classic psychedelic-related seizures were more commonly reported in certain respondents, especially those with a personal or family history of epilepsy. Conclusions: These results suggest that classic psychedelic use could increase the risk of seizures in certain populations, particularly those with a personal or family history of epilepsy. Highlights: Low prevalence of classic psychedelic-related seizures (1.5 %). Classic psychedelic-related seizures more common among those with a personal or family history of epilepsy. Co-use of certain widely-prescribed medications common during classic psychedelic-related seizures.